Robot-assisted track-scan imaging approach with multiple incident angles for complexly structured parts - Mei, Yujian (2022)
The ever-increasing use of complexly structured parts in modern manufacturing introduces new challenges to the inspection. However, high detection coverage and the contrast of ultrasonic images cannot be obtained by conventional B-scan imaging. To improve the quality of ultrasonic imaging of nonplanar components, we propose a robot-assisted track-scan imaging approach with multiple incident angles, and we have developed an ultrasonic data acquisition platform to implement it. The main idea of this method is to use multiple incident angles to improve the transfer of wave energy into the sample. Using rich information gathered from different incident angles, a nonplanar surface is correctly imaged by the proposed method. As seen from the experimental results, the proposed method can increase the detection coverage and contrast of images. Comparing different scanning trajectories and imaging methods, the detection coverage is improved by up to 57.3% and 88.7% for curved and inclined surfaces, respectively, by the proposed method. Similarly, the contrast-to-noise ratio increases up to 8.04 dB and 8.58 dB, respectively. Thus, our method has great potential for application in nondestructive ultrasonic imaging of complex-structure parts.